Cultivation of a vampire: 'Candidatus Absconditicoccus praedator'. (9th November 2021) - Yakimov, Michail M.; Merkel, Alexander Y.; Gaisin, Vasil A.; Pilhofer, Martin; Messina, Enzo; Hallsworth, John E.; Klyukina, Alexandra A.; Tikhonova, Ekaterina N.; Gorlenko, Vladimir M.
Summary: Halorhodospira halophila, one of the most‐xerophilic halophiles, inhabits biophysically stressful and energetically expensive, salt‐saturated alkaline brines. Here, we report an additional stress factor that is biotic: a diminutive Candidate‐Phyla‐Radiation bacterium, that we named ' Ca . Absconditicoccus praedator' M39‐6, which predates H . halophila M39‐5, an obligately photosynthetic, anaerobic purple‐sulfur bacterium. We cultivated this association (isolated from the hypersaline alkaline Lake Hotontyn Nur, Mongolia) and characterized their biology. 'Ca . Absconditicoccus praedator' is the first stably cultivated species from the candidate class‐level lineage Gracilibacteria (order‐level lineage Absconditabacterales). Its closed‐and‐curated genome lacks genes for the glycolytic, pentose phosphate‐ and Entner–Doudoroff pathways which would generate energy/reducing equivalents and produce central carbon currencies. Therefore, 'Ca . Absconditicoccus praedator' is dependent on host‐derived building blocks for nucleic acid‐, protein‐, and peptidoglycan synthesis. It shares traits with (the uncultured) ' Ca . Vampirococcus lugosii', which is also of the Gracilibacteria lineage. These are obligate parasitic lifestyle, feeding on photosynthetic anoxygenic Gammaproteobacteria, and absorption of host cytoplasm. Commonalities in their genomic composition and structure suggest that the entire Absconditabacterales lineage consists of predatory species which act to cull the populations of their respective host bacteria. Cultivation of vampire : host associations can shed light on unresolved aspects of their metabolism and ecosystem dynamics at life‐limiting extremes.